Ocena stanu wiedzy pacjentów na temat profilaktyki osteoporozy = Assessment of patients’ knowledge about the prevention of osteoporosis - Srokowska, Anna; Zawadzka, Emilia; Lewandowski, Andrzej; Kowalik, Tomasz; Siedlaczek, Marcin; Srokowski, Grzegorz; Radzimińska, Agnieszka; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Srokowska Anna, Zawadzka Emilia, Lewandowski Andrzej, Kowalik Tomasz, Siedlaczek Marcin, Srokowski Grzegorz, Radzimińska Agnieszka, Zukow Walery. Ocena stanu wiedzy pacjentów na temat profilaktyki osteoporozy = Assessment of patients’ knowledge about the prevention of osteoporosis. Journal of Education, Health and Sport. 2015;5(12):503-520. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.42265 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A503-520 http://pbn.nauka.gov.pl/works/686220 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 15.12.2015. Accepted: 23.12.2015. Ocena stanu wiedzy pacjentów na temat profilaktyki osteoporozy Assessment of patients’ knowledge about the prevention of osteoporosis 1Anna Srokowska, 2Emilia Zawadzka, 1Andrzej Lewandowski, 1Tomasz Kowalik, 2Marcin Siedlaczek, 2Grzegorz Srokowski, 2Agnieszka Radzimińska, 3Walery Zukow 1Z Katedry i Zakładu Podstaw Kultury Fizycznej UMK w Toruniu Collegium Medicum im. L. Rydygiera w Bydgoszczy, Polska 2Z Katedry Fizjoterapii, Zakładu Kinezyterapii i Masażu Leczniczego UMK w Toruniu Collegium Medicum im. L. Rydygiera w Bydgoszczy, Polska 3Z Wydziału Kultury Fizycznej, Zdrowia i Turystyki Uniwersytetu Kazimierza Wielkiego w Bydgoszczy, Bydgoszcz, Polska Adres do korespondencji: 1. mgr Anna Srokowska, Katedra i Zakład Podstaw Kultury Fizycznej UMK w Toruniu Collegium Medicum im. L. Rydygiera w Bydgoszczy, ul. Świętojańska 20, 85-077 Bydgoszcz, tel. 600341155, e-mail a.srokowska@cm.umk.pl 2. dr Grzegorz Srokowski, Katedra Fizjoterapii, Zakład Kinezyterapii i Masażu Leczniczego UMK w Toruniu Collegium Medicum im. L. Rydygiera w Bydgoszczy, ul. Techników 3, 85-801 Bydgoszcz, tel. 608591155, e-mail g.srokowski@gmail.com Słowa kluczowe: osteoporoza, profilaktyka. Streszczenie Osteoporoza to choroba charakteryzująca się zmianami w strukturze tkanki kostnej, które zwiększają ryzyko złamań. Złamania osteoporotyczne są przyczyną stresu i bólu, a leczenie bywa długie i kosztowne. Dlatego bardzo ważna jest profilaktyka osteoporozy. Poszerzenie wiedzy na ten temat pomaga pacjentom unikać niebezpieczeństw wynikających z tej choroby. Celem pracy była ocena stanu wiedzy pacjentów na temat profilaktyki osteoporozy. Badaniem objęto 72 pacjentów korzystających z usług Poradni Rehabilitacyjnej w Sierpcu. Stan wiedzy pacjentów znajdujących się w grupie ryzyka sprawdzono za pomocą ankiety. Wyniki badań przeprowadzone w niniejszej pracy wskazują, że wiedza pacjentów na temat profilaktyki osteoporozy jest niska. Poziom ogólnej wiedzy badanych, biorąc pod uwagę zmienne społeczno-demograficzne, zależny jest od ich płci. Z badań wynika, że kobiety znacznie więcej wiedzą na temat osteoporozy w porównaniu do mężczyzn. Nie wykazano istotnych różnic w wiedzy ogólnej dotyczącej osteoporozy w zależności od wieku, miejsca zamieszkania oraz wykształcenia. W profilaktyce osteoporozy, należy zwrócić uwagę na poszerzenie świadomości pacjentów na temat tej choroby. Każdy pacjent znajdujący się w grupie ryzyka powinien poszerzyć swoją wiedzę o problemie jakim jest osteoporoza, w celu zminimalizowania ryzyka powikłań, w szczególności złamań osteoporotycznych. Keywords: osteoporosis, prevention. Abstract Osteoporosis is a disease characterized by changes in the structure of bone tissue, which increases the risk of fractures. Osteoporotic fractures are the cause of stress and pain and the treatment is sometimes long and costly. Therefore it is very important to the prevention of osteoporosis. Expanding knowledge on the subject helps patients avoid the dangers of the disease. The aim of the study was to assess the state of patients’ knowledge about the prevention of osteoporosis. The study included 72 patients using the services of Rehabilitation Clinic in Sierpc. The state of patients who are at risk verified by the survey. The results of research conducted in this study indicate that patients knowledge about the prevention of osteoporosis is low. The level of general knowledge studied, taking into account the variables of socio - demographic, is dependent on their sex. Research shows that women are much more knowledgeable about osteoporosis compared to men. There were no significant differences in general knowledge on osteoporosis, depending on age, place of residence and education. The prevention of osteoporosis, you should pay attention to the expansion of patient awareness about the disease. Each patient is located in the risk group should expand their knowledge no problem what is osteoporosis, in order to minimize the risk of complications, particularly osteoporotic fractures.